Religion, Tradition, and Language as Aspects of Formation and Preservation of the National Identity of Kosovo and Metohija Inhabitants - Bojičić, Radica R.; Aleksić, Ivana D. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The socio-economic changes that mark life in the 21st century and cause new cultural patterns that affect the preservation of identity as a process of formation, actually the acquisition of identity self-awareness and distinguishability, defy the complexity of identity, whose topicality in the last few years testifies that the mentioned phenomenon does not have the characteristics of “overcome creation of the past”. Although religious affiliation is often stated as an essential sign of individual and group self-recognition, tradition and language as integral parts of cultural heritage, which speaks of the history and permanence of a people, represent aspects whose influence on the formation of identity must not be ignored. Given that the territory of Kosovo and Metohija is not ethnically pure and it is inhabited by members of different religions and cultures, the study conducted for the purposes of this paper included Orthodox and Muslim participants who expressed their views on the role of religion, tradition and language in the preservation of their national identity. Based on the results of the research, the authors provide an analysis of the importance of all three above-mentioned aspects in the formation and preservation of the national identity of the people in Kosovo and Metohija.
Keywords: national identity; Orthodox; Muslims; religion; tradition; script; Kosovo and Metohija